Comparison of ruminal microbiota, metabolomics, and milk performance between Montbéliarde×Holstein and Holstein cattle - Chang, Haomiao; Wang, Xinling; Zeng, Hanfang; Zhai, Yunfei; Huang, Ni; Wang, Changjian; Han, Zhaoyu (Frontiers in Veterinary Science, 2023)
This experiment crossbred Holstein with Montbéliarde cattle, aimed to act as a reference for producing high-quality dairy products and improving the overall efficiency of dairy cattle breeding. Based on similar age, parity and lactation time, 46 cows were selected and divided into two groups (n = 23 per group) for comparison experiment and fed the same formula: Montbéliarde×Holstein (MH, DIM= 33.23 ± 5.61 d), Holstein (H, DIM = 29.27 ± 4.23 d). Dairy herd improvement (DHI) data is an important basis for evaluating the genetic quality of bulls, understanding the quality level of milk, and improving feeding management. We collected the DHI data of these cows in the early lactation, middle lactation and late lactation period of 10 months. The results showed that the average milk production and protein content in Montbéliarde×Holstein were 1.76kg (34.41kg to 32.65kg, P>0.05) and 0.1% (3.54% to 3.44%, P<0.05) higher than in Holstein cattle. Moreover, milk from Montbéliarde×Holstein cattle had lesser somatic cell score (1.66 to 2.02) than Holstein cattle (P<0.01). A total of 10 experimental cattle in early lactation were randomly selected in the two groups (Lactation time = 92.70 ± 6.81), and ruminal fluid were collected by oral gastric tube. Using 16S rRNA microbial sequencing, we compared the ruminal microbiota composition and found that Montbéliarde×Holstein cattle had a lower abundance of Alphaproteobacteria (P<0.05) and higher abundance of Selenomonas than Holstein cattle (P<0.05). These bacteria play roles in protein degradation, nitrogen fixation and lactic acid degradation. The abundance of Succiniclasticum was also greater in Montbéliarde×Holstein cattle (P=0.053). Through ruminal metabolome analysis, we found that the levels of trans-ferulic acid, pyrrole-2-carboxylic acid, and quinaldic acid were significantly increased in Montbéliarde×Holstein cattle, while that of lathosterol was significantly decreased.The changes in the levels of these metabolites could confer improved antioxidant, antiinflammatory, and antibacterial activities.